Component-resolved bleaching correlation between OSL and IRSL signals in various geological materials. (January 2019) - Angeli, V.; Kitis, G.; Polymeris, G.S.; Şahiner, E.; Meriç, N.
Abstract: The primary aim of the present study includes establishing a qualitative as well as quantitative correlation between OSL and IRSL signals in various materials of geological origin, by investigating the influence of the IR stimulation to the OSL signal. The materials which are the subject of the present study include one K-feldspar belonging to the group of microcline, two different grain size fractions of Durango apatite at the edge of the nano-scale and gypsum. A two-step stimulation protocol was applied, including an exposure of the irradiated sample to infrared stimulation for various time and a subsequent continuous wave OSL using blue light. In the framework of a component-resolved analysis, the IRSL decay curves were fitted using analytical equations describing the localized tunneling recombination model; the subsequent OSL decay curves were also fitted using a linear superposition of analytical expressions describing both delocalized and localized recombination processes. The selection of number and type of components in the latter case is also elaborated, based on the physical meaningfulness of the de-convolution results. Highlights: Combined OSL and IRSL measurements on 4 different cases of naturally occurring minerals were performed. IRSL depletes partially the fast OSL components. The selection of number and type of components of both IRSL and OSL signals was justified. Structural characterization is possible using de-convolution results.